Does peers’ sexual behaviors affect adolescents’ sexual behaviors? - Joshi, S. (Journal of Institute of Medicine Nepal, 2007)
This study is aimed to determine female adolescents’ reproductive and sexual health behaviors in order to promote healthy reproductive behaviors. A descriptive correlation design was used to identify the main predictor of female adolescents’ reproductive and sexual health behaviors. Four hundred samples were selected from urban government schools of Lalitpur; findings revealed that more then half of respondents (56%) felt very comfortable to communicate with their peer than others. There were statistically significant relationships between female adolescents’ with their peers’ reproductive and sexual health behaviors (r = 0.646; p = Journal of Institute of Medicine Vol.27(2) 2005